2005
DOI: 10.1152/ajpgi.00017.2005
|View full text |Cite
|
Sign up to set email alerts
|

P2X2receptors are essential for [Ca2+]iincreases in response to ATP in cultured rat myenteric neurons

Abstract: ]i similar to that induced by P2Y agonists. At Ϫ60 mV, ATP evoked a slowly inactivating inward current that was suppressed by the removal of extracellular Na ϩ concentration. The current-voltage relation for ATP showed an inward rectification with the reversal potential of about 0 mV. The apparent rank order of potency for the purinoceptor agonist-induced increases of [Ca 2ϩ ]i was ATP Ն adenosine 5Ј-O-3-triphosphate Ն CTP Ն 2-methylthio-ATP Ͼ benzoylbenzoyl-ATP. A similar potency order was obtained with cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 63 publications
3
19
0
Order By: Relevance
“…1A,B), but not GTP- and UTP-evoked currents (Fig. 1C,D), consistent with the previous electrophysiological analyses of P2X receptors1617182223242526.…”
Section: Resultssupporting
confidence: 91%
“…1A,B), but not GTP- and UTP-evoked currents (Fig. 1C,D), consistent with the previous electrophysiological analyses of P2X receptors1617182223242526.…”
Section: Resultssupporting
confidence: 91%
“…Studies using P2X2 receptor knockout mice showed that P2X2 receptors contribute to fast synaptic excitation of myenteric neurons in small intestine [572]. P2X2 homomeric receptors appear to be the predominant receptors mediating fast synaptic excitation in the gut [248,250,524]. Intrinsic sensory neurons in the gut, identified as Dogiel type II neurons, express P2X2 receptors [237].…”
Section: Enteric Gangliamentioning
confidence: 99%
“…Several studies have proposed a role for homomeric P2X 2 , and possibly heteromeric P2X 2 -containing channels, in ATP-mediated facilitation of inhibitory γ-amino butyric acid-mediated (GABAergic) synaptic transmission in the hippocampus and dorsal horn [8,22,133,167]. P2X 2 is also heavily expressed in the peripheral nervous system on both sensory and autonomic ganglion neurons [45,59,63,201,202,270,313,330,[336][337][338][339], signifying roles in afferent and efferent signaling pathways, and in the enteric nervous system where homomeric P2X 2 channels are thought to mediate fast synaptic excitation on S-type myenteric neurons [48,94,233,250,340]. Numerous recent studies have implicated both peripheral and central P2X 2 channels in chemosensory transduction in a variety of physiological systems, including the regulation of respiratory control in response to hypoxia and hypercapnia (via sensory neurons within neuroepithelial bodies and the carotid body and the ventrolateral medulla) [107,121,205,242,258,335], and in the detection of chemical stimuli, such as odorants (via trigeminal neurons in the nasal epithelium) [279], and taste (by gustatory nerves) [86].…”
Section: Inhibitionmentioning
confidence: 99%